Can hepatitis B virus DNA in semen be predicted by serum levels of hepatitis B virus DNA, HBeAg, and HBsAg in chronically infected men from infertile couples?. (14th April 2015) - Fei, Q.J.; Yang, X.D.; Ni, W.H.; Pan, C.S.; Huang, X.F.
Summary: Hepatitis B virus (HBV) in semen is important for father‐to‐child transmission of HBV and has adverse effects on sperm quality. However, risk factors associated with HBV in semen remain unclear. Serum HBV DNA and hepatitis B e antigen (HBeAg) levels may pose a risk on HBV in semen. This study aims to examine whether serum HBV DNA, HBeAg, and hepatitis B surface antigen (HBsAg) level were associated with HBV DNA in semen. 151 male patients chronically infected with HBV from infertile couples were included. Serum HBsAg and HBeAg were determined using an electrochemiluminescence immune assay (ECLIA). Serum and seminal plasma HBV DNA were detected by the QIAGEN Real‐Time HBV DNA assay. Of 151 patients, 143 (94.7%) were serum HBV DNA‐positive and 65 (43.0%) were seminal plasma HBV DNA‐positive. Serum HBV DNA and HBeAg level of seminal plasma HBV DNA‐positive patients were significantly higher ( p  <   0.001) as compared with those of seminal plasma HBV DNA‐negative patients, HBsAg level of seminal plasma HBV DNA‐positive patients was significantly lower ( p  <   0.001) compared with that of seminal plasma HBV DNA‐negative patients. The best serum HBV DNA, HBeAg, and HBsAg value for discriminating between seminal plasma HBV DNA‐positive and HBV DNA‐negative patients were ≥6.9 log10 IU/mL (sensitivity 100.0%, specificity 90.7%), >14.8 S/CO (sensitivity 96.9%, specificity 81.5%), and <1791.5 S/CO (sensitivity 81.5%, specificity 81.2%), respectively. The combination of serum HBV DNA and HBeAg had high diagnostic sensitivity (100.0%) and specificity (95.4%) for the presence of HBV DNA in semen. As such, these serum markers especially the combination of HBV DNA and HBeAg are useful predictors of the presence of HBV DNA in semen in HBV chronically infected men from infertile couples.